Mutational profile of pfdhfr, pfdhps, pfmdr1, pfcrt and pfk13 genes of P. falciparum associated with resistance to different antimalarial drugs in Osun state, southwestern Nigeria - Alexandra Martín Ramírez; Akeem Abiodun Akindele; Vicenta González Mora; Luz García; Nicole Lara; Eva de la Torre-Capitán Matías; Irene Molina de la Fuente; Sulaiman Adebayo Nassar; Thuy-Huong Ta-Tang; Agustín Benito; Pedro Berzosa (Tropical Medicine and Health)
Abstract Background Nigeria accounts for the greatest burden of malaria disease globally. Malaria control requires an effective treatment after diagnosis. The efficacy of antimalarial drugs can be assessed through the analysis of genetic changes associated with reduced drug sensitivity. Methods This study includes the analysis of the markers associated with artemisinin (pfk13), sulfadoxine–pyrimethamine (pfdhfr and pfdhps), and chloroquine and its derivatives (pfmdr1 and pfcrt) resistances, in blood samples collected from asymptomatic children in south-western Nigeria. Results The 25.95% of samples showed a number of mutations in pfk13 gene. Among those, the validated, C580Y, and the candidate, R515K, mutations by WHO were detected. Twenty-seven pfdhps different haplotypes were observed, with the haplotype ISGKAA as the most prevalent (18.80%), followed by IFGKAA (12.78%) and IAGKAA (11.28%). The VAGKGS was the most common haplotype carrying the I431V mutation (10.53%). Combinations of alleles in pfdhfr and pfdhps genes provided a 40.98% of samples with the partially resistant haplotype (IRNG). No samples exhibited the ‘fully resistant’ or ‘super resistant’ pfdhprf–pfdhps combinations, but one sample contained mutations at pfdhfr 51I, 59R, and 108N with pfdhps 431V, 436A, A437G and 540E. The analysis of pfcrt 72–76 variants disclosed a 12.12% of samples with the mutant-type (CVIET). No double mutant pfmdr1 haplotypes 86Y/1246Y (YY) were detected, nor was the haplotype formed by the alleles 86Y pfmdr1 + pfcrt 76 T (YT). Conclusions There was no evidence of parasite genomes harbouring multilocus mutations conferring multidrug resistance, although evidence of a validated (C580Y) and a candidate (R515K) mutation in pfk13 gene, high frequency pfdhfr mutant alleles and high variability of pfdhps haplotypes were found in this study, which provides a baseline information essential in monitoring P. falciparum resistances.